Lost and Found in Upstate New York: Exploring the Motivations of "Lost Boys" Refugees as Founders of International Nonprofit Organizations. Issue 8 (September 2020) - Appe, Susan; Oreg, Ayelet
This research examines engagement in diaspora philanthropy through the lens of Lost Boys of Sudan and their founding of small international nonprofit service organizations based in the United States. We seek to understand refugees' motivations to take upon themselves leadership roles in their local United States communities and in the provision of goods and services to their homeland, South Sudan. By becoming founders of international service nonprofits, Lost Boys make meaning of their experiences and are able to motivate local support in their United States communities to give to distant communities in South Sudan.